Tinjauan Hukum terhadap Kewenangan Jaksa Pengacara Negara dalam Kasus Tata Usaha Negara - Rahmawati, Dyah; Holijah, Holijah (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2025)
ABSTRACT; This study examines the authority of the State Attorney (JPN) in handling administrative disputes, particularly in Case Number 6/6/2021/PTUN PLG, which involves an administrative dispute between the government and society. In this context, JPN plays a crucial role in ensuring that government policies remain legitimate and do not violate citizens' constitutional rights. This study highlights how JPN, as the representative of the state, acts when facing lawsuits against administrative policies deemed harmful to certain parties. Additionally, the study evaluates the challenges faced by JPN in exercising its authority, such as differences in legal interpretation and resource limitations, and how JPN maintains a balance between the interests of the state and individual rights. The findings of this study provide insight into JPN's contribution to maintaining the government's authority and the importance of JPN's role in ensuring that government policies align with applicable legal principles, strengthening the credibility and legitimacy of the government in the eyes of the public.